Social Prescription Interventions: A Systematic Literature Review. - SANTANA RUIZ, ANA PINHEIRO; DE ASSIS, RODRIGO VIEIRA; CIFUENTES-TINJACA, CRISTIAN DAVID; ROSINHA, ANTÓNIO PALMA (Salud Uninorte)
Introduction: The increasing health disparities underscore the importance of preventive interventions, where social prescription (SP) emerges as a comprehensive intervention for physical, mental, and social health. Objective: Identify the application procedures, types of interventions, and results of SP studied in the literature between 2019 and 2023. Materials and methods: In this systematic review, the inclusion criteria consisted of samples of adults with any medical condition, studies available in Portuguese, English, or Spanish, and those describing the direct impact of an SP intervention on clients. The investigation period was from July 12 to September 1, 2023, and the databases used were Academic Search Complete, Web of Science, PubMed, and Scopus. Results: Eight articles involving 352 participants (SD=442.648) were selected. We identified studies of a qualitative (37.5%), quantitative (37.5%), and mixed (25%) nature. Qualitative studies analyzed the experiences and perceptions of clients and liaison workers regarding the SP intervention, while quantitative studies assessed the effects of SP on variables such as mental and physical health, and social well-being. Mixed studies analyzed physical health, identification, and social belonging. We identified wide-ranging benefits, including improvements in mental and physical health, self-determination, autonomy, and social well-being. Conclusions: SP has demonstrated the potential to improve health and well-being individually and systemically, thereby increasing the efficiency of healthcare services. However, adaptation to individual needs and the effective integration of healthcare and community support are essential. The limitations suggest the need for future research addressing additional criteria.